Clinical Profile of Patients Presenting to Low Vision Clinic of a Tertiary Center in Western Region of Nepal - Thapa, HB; Gautam, P; Mahotra, NB; Bajracharya, K (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Low vision is an important public health problem; however, very few low vision clinics are available to address the needs of low vision patients in most developing countries. The purpose of this study was to describe the characteristics of patients attending the low vision clinic of a tertiary care eye hospital of Western Region of Nepal. METHODS: This was a prospective cross sectional study of all new Nepali patients seen at the low vision clinic over 2 years period. The patients were administered with clinical low vision form (a structured questionnaire) and were examined and tested with low vision devices by the attending low vision specialist. Information on the demographic and clinical characteristics of the patients was recorded. RESULTS: A total of 214 new patients seen during the period were studied. The mean age was 19.80 years, and their ages ranged between 4 and 86 years with a male to female ratio of 2.69:1. Majority (53.30%) were children (≤15years), while 3.70% were elderly patients (≥65years). The commonest cause of low vision was lens related like pseudophakia, aphakia (20.60%); 18.20% had refractive error/amblyopia; 17.80% had retinitis pigmentosa; macular disorder (20%) and retinitis pigmentosa (20%) were the commonest cause in the adult and elderly patients, while lens related (24.6%) and refractive error/amblyopia (21.1%) were the commonest causes in children. CONCLUSION: The demographic and clinical characteristics of low vision patients seen in this clinic are similar to that of patients in other developing countries, but different from those in developed countries. Elderly patients and females may be under-utilizing low vision services. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11172 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 35-39